Web-based Context-Aware m-Learning Architecture - Basaeed, Eisa; Berri, Jawad; Zemerly, Jamal; Benlamri, Rachid (International Journal of Interactive Mobile Technologies (iJIM), 2007)
Context awareness is essential in mobile learning being a highly personalized environment with diverse capabilities. Major challenges of context awareness are to define the learning context, how to sense it, and how to react to changes. Our proposed system provides a general architecture that facilitates contextualization using current widely-used web standards. It provides a systematic approach to achieve contextualization defining major components and their functionalities without deepening into details. It uses web services to connect to resources making them reusable and distributable. In addition, all technologies and platforms proposed in our system are available under General Public License (GPL) hence facilitating immediate implementation. The paper ends with a real world scenario where m-Learning could be the only solution.